Solid Lipid Nanoparticles Based on L-Cysteine for Progesterone Intravaginal Delivery - Roberta Cassano; Sonia Trombino (International Journal of Polymer Science)
The present work has as its purpose the synthesis and characterization of a novel lipid material to be used in the preparation of solid lipid nanoparticles (SLNs) for the potential sustained release of progesterone in the vagina. For this reason, a material capable of ensuring the permanence of the formulation in the administration site for the time needed to guarantee the transmucosal absorption of the steroid was synthetized in order to reduce the number of administrations and to ensure an effective concentration of drug at the site of action. To this end, an ester, 2,3-dihydroxypropanoate of octadecyl (stearyl glycerine), containing two hydroxyl groups was initially synthesized. In particular, the hydroxyl group less sterically encumbered was functionalized with a thiol group, in a coupling reaction, with the amino acid L-cysteine. The obtained compound was characterized by FT-IR spectrometry and 1H-NMR. The functionalized lipid with L-cysteine was then used for the preparation of solid lipid nanoparticles that were loaded with progesterone. Finally, the release of progesterone from the lipid matrix based on newly synthesized ester, under conditions that simulate the vaginal physiological environment, was evaluated. All the obtained results suggest that the prepared nanoparticles could be used for the administration of progesterone, when its integration is essential, for example, in cases of threats of abortion or to increase fertility.